Breast cancer screening and diagnosis in older adults women in Brazil: why it is time to reconsider the recommendations - Aline Ferreira Bandeira Melo Rocha; Ruffo Freitas-Junior; Leonardo Ribeiro Soares; Glalber Luiz Rocha Ferreira (Frontiers in Public Health, 2023)
IntroductionBreast cancer screening in women of 70 years of age or older remains controversial due to a lack of studies that include women of this age.MethodsThis ecological study evaluated data from the Brazilian National Health Service (SUS) on breast cancer screening and staging in this age group compared to 50–69-year olds, for Brazil as a whole and for its geographical regions, between 2013 and 2019. A secondary database was obtained from the outpatient data system of the SUS’s Informatics Department, the Brazil Oncology Panel, the Brazilian Institute of Geography and Statistics, the Supplementary Health Agency and the Online Mortality Atlas.ResultsThere was a marked reduction in screening in women ≥70 years of age (annual percent change [APC] –3.5; p < 0.001) compared to those of 50–69 years of age (APC-2.2; p = 0.010). There was a trend towards an increase in clinical staging, with a greater occurrence of stages III and IV in the ≥70 group (44.3%) compared to the women of 50–69 years of age (40.8%; p < 0.001).ConclusionConsidering the increasing age of the Brazilian population and the heterogeneity among older adults women, screening for the over-70s within the SUS merits greater debate insofar as the implementation of public policies is concerned.